The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/nph.12042
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics and age of stemwood nonstructural carbohydrates in temperate forest trees

Abstract: SummaryNonstructural carbohydrate reserves support tree metabolism and growth when current photosynthates are insufficient, offering resilience in times of stress.We monitored stemwood nonstructural carbohydrate (starch and sugars) concentrations of the dominant tree species at three sites in the northeastern United States. We estimated the mean age of the starch and sugars in a subset of trees using the radiocarbon ( 14 C) bomb spike.With these data, we then tested different carbon (C) allocation schemes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
376
4
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(406 citation statements)
references
References 64 publications
23
376
4
3
Order By: Relevance
“…They found that leaf phenology, NSC storage and intra-annual growth were clearly different between species, highlighting their contrasting carbon allocation. Very recently, the seasonal dynamics and ages of stemwood NSC in temperate forest trees has been assessed by Richardson et al (2013). These authors found that NSC were both highly dynamic and about a decade old.…”
Section: Does Leaf Production Impact Wood Production?mentioning
confidence: 97%
“…They found that leaf phenology, NSC storage and intra-annual growth were clearly different between species, highlighting their contrasting carbon allocation. Very recently, the seasonal dynamics and ages of stemwood NSC in temperate forest trees has been assessed by Richardson et al (2013). These authors found that NSC were both highly dynamic and about a decade old.…”
Section: Does Leaf Production Impact Wood Production?mentioning
confidence: 97%
“…Similarly, we calculated that the size of the NSC pool in branches + stems were 4.6-and sixfold greater than the C pools in the leaf canopy of larch and ash, respectively. However, the residence time of NSC storage could be several years, and only a small fraction of the NSC pool is likely to be mobilized during a growing season under normal conditions (Würth et al 2005;Vargas et al 2009;Richardson et al 2013). In our study, the NSC mobilized from storage organs from mid-May to mid-June accounted for 20 and 31 % of the whole-tree NSC pool in larch and ash, respectively, which are comparable to values (less than one-third) reported in other studies (Hoch et al 2003;Würth et al 2005;Körner 2003).…”
Section: Seasonal Dynamics Of the Sizes Of Nsc And N Pools In Differementioning
confidence: 99%
“…These strategies differ in the number of storage compartments, Storage: 0, Storage: 1, and Storage: 2. Adapted from (Richardson et al, 2013). The parameters are the rates at which the carbon cycles into and out of the compartments; thus, the fluxes are proportional to the C stocks and the rates.…”
Section: Methodsmentioning
confidence: 99%
“…We implemented three models whose carbon allocation strategies varied depending on the number of storage compartments (0, 1, or 2) (Figure 2), following the hypotheses proposed by Richardson et al (2013). The core structure of the models is a constant photosynthetic input -gross primary production (GPP): u-of 1400 gCm −2 year −1 (Urbanski et al, 2007), which enters the system through the Photoassimilates compartment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation